Groundwater Quality Analysis Based on Physical Properties of The Gunungtiga and Surrounding Areas - Hilman, Zaki; Widiatama, Angga Jati; Awfa, Dion; Alfarishi, Bilal; Prayogo, Wisnu; Depri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Gunungtiga area has never been studied for the quality of groundwater, and residents have also complained about the quality of groundwater, these became the basis for selecting the research location. This study aims to analyze groundwater quality in the Gunungtiga Region, Lampung Province. Quantitative approached was used for this research, it was carried out by mapping the groundwater level to estimate the recharge area and collecting data on parameters of the physical properties of groundwater, including color, taste, odor, temperature, pH, TDS, and EC. The physical properties approach was selected because it is relatively cheap and easy to observe, the data collection can also be done in situ. The physical property parameter data is then checked based on the Republic of Indonesia Minister of Health Regulation No. 492 of 2010. The observations at 14 points showed that the groundwater level in the research area is relatively shallow towards the west or in the direction with higher topography, so it can be interpreted as a recharge area, and it flowed towards the east area which has lower topography. The physical properties of the groundwater had no taste, odor, or color. The EC value ranges from 188.07 to 1066.82 µs/cm, including fresh water, the pH ranges from 5.41 to 7.5, the temperature ranges from 27.2 to 29.7 0C, and the TDS value ranges from 94. 04-542.91 mg/l. Of the 14 observation points, only 1 location met the quality standards, namely 22/DP/02. Treatment is required before groundwater can be used, such as filtering.